Tempo de residência e estabilização do carbono em solos da Amazônia - Luz, Fernanda Michele (Clima e Ambiente - CLIAMB, 2018)
Soils in the Amazon vary according to pedogenetic levels and nutrient content of soils. The ability of Amazonian soils to stabilize carbon is of great importance in this context. The carbon stocks (C) of the Amazonian soil are similar or even higher than the estimates of above-ground biomass for the entire Amazon region, which are about 90 Pg of C, making the Amazon one of the largest reservoirs of C between terrestrial ecosystems, having important implications in scenarios of climate change and land use. Radiocarbon (14C) is a useful tool for studying the exchange of C between terrestrial ecosystems and the atmosphere over long time scales. Tests of above-ground nuclear weapons in the early 1960s nearly doubled the amount of 14C in the atmosphere. This increase of 14C caused by anthropic activity is called Bomb-14C and function as a tracer, usually corresponding to the modern fraction (F14C) of C in soil organic matter. Radiocarbon analyzes were used in this work to determine the residence time of C in soils and to explain the stabilization processes between organic matter and minerals in soils with different levels of pedogenetic development. As soils and ecosystems develop, they gain and lose C, being interactions with the quantity and quality of the organic material entering the soil and its rate of mineralization, which can be reduced or controlled by stabilization processes that protect carbon (COS) of microbial decomposition. It is known that C stabilization in soils is related to minerals and oxides and hydroxides of iron (Fe) and aluminum (Al) and is particularly related to properties such as mineralogy, clay content, specific surface area and the processes of weathering. In this work, young and old soils with ilite-smectite and kaolinite mineralogy were selected, with clays with low to moderate weathering levels and well-weathered clays in soils with a high level of development, respectively. In each study area soil profiles with depths of 0 to 150 cm were selected. In general, the main processes controlling COS storage are related to the content of kaolinite-dominated clays (R2 = 0.91 and p <0.002) and amorphous Feo oxides, (R2 = 0.72 and p <0.003, Clay + Fed, R2 = 0.74 and p <0.01) in all profiles, declining COS with depth. The 14C present on the soil surface represent the values of the modern carbon fraction, residence time in a reservoir of active COS, in annual to decadal scales, the ratio is significant with [C] / Clay (R2 = 0.53 and p < 0.010 and with Alp (Al-hummus) (R2 = 0.64 and p <0.009). For the layers from 50 to 150, F14C is related to [C] / Clay (R2 = 0.40 and p = 0.04) and significantly correlated with Fed and Fed-o (crystalline) and Fep, probably representing a continuous free Fe, Fe-humus and C complexes associated with the specific surface of Fe oxides. It is concluded that older, weathered soils of the Amazon rainforest, dominated by kaolinite, have the largest carbon stocks, and greater stability of F14C for long residence time (passive pools in timescales of millennia). In general, younger soils from the west of the basin (less weathered) have less ability to stabilize C for long time. The COS stabilization processes associated with the physical properties of soils occur according to the differences in the level of weathering, mineralogy of the soils and the time of the COS, which has great implications in scenarios of climate change and land use.
Residence time and carbon stabilization in Amazonian soils
Keywords: Estabilizaçã do carbono nos solos; Carbono orgânico em solos da Amazônia; Radiocarbono; Carbono 14 Fração Moderna